Maneuvering with crime: an empirical reconstruction of “populist” stances on youth crime in German parliamentary debates - Dollinger, Bernd (European journal on criminal policy and research, 2017)
Recent years have seen a wide discussion of populism in penal policy, which is internationally regarded as a strong drive for establishing punitive tendencies. Generally, “penal populism” is characterized by an extensive consensus across the most influential political parties, a punitive orientation, and the dismissal of scientific or professional expertise. Recent penal policy therefore appears to be a relatively unified practice strongly oriented toward punitive measures that primarily address the public and its perceived need for protection. Because analyses of Anglophone countries are predominant in this discussion, we contrast them with a reconstruction of debates on youth crime in German parliaments from 1970 to 2012. They exhibit a wide variety of populist articulations. Although they imply a strong punitive bias, they also encompass a very heterogeneous rhetoric of penal policy. In conclusion, we argue that penal populism can (and should) be described as a tactical practice, i.e., as political maneuvering employed to negotiate the prospects of punitive and other styles of politics.